The paradox of regional investment in regional-owned enterprises: Implications of capital participation for local own-source revenue and the strategic role of internal auditors - evidence from regional-owned enterprises in Central Sulawesi Province - Naela Zaqiyatul Misqiyah; Nural Achmad Raainaa (PT Wim Solusi Prima, 2026)
Regional government officials are often confronted with a contradiction between high levels of government investment and the limited financial returns generated for Local Own-Source Revenue (PAD). This phenomenon reflects a gap between the objective of regional capital participation as an instrument for strengthening the local economy and the reality of the still-low contribution of Regional-Owned Enterprises (BUMD) to regional revenue. This qualitative study, employing a literature review approach, aims to examine the anomaly of capital capitalization in BUMD within Central Sulawesi Province and to formulate the role of internal auditors in addressing this issue. The analysis was conducted through a review of regional government financial statements, BUMD capital participation and dividend data, relevant regulations, and various literature related to regional corporate governance and internal auditing. The explanatory findings indicate that BUMD have not yet been able to formulate a rigid and sustainable business model and have failed to optimize public value following capital injections. This condition is reflected in the low contribution of dividends to PAD, the high dependence on a single productive BUMD entity, and the existence of regional enterprises that continue to incur losses despite receiving significant capital support from the regional government. This situation indicates weak implementation of corporate governance, an unclear business direction, and the still-limited effectiveness of oversight mechanisms. To address this governance urgency, internal auditors occupy a strategic position as catalysts for organizational change. The acceleration of BUMD performance can be achieved through the establishment of a structured intervention model encompassing diagnostic audits, governance assessments, business feasibility reviews, performance monitoring systems, and strategic recommendations. This model is expected to encourage the transformation of BUMD from a fiscal burden into creators of sustainable economic value for the region.